THE EFFECTIVENESS OF USING SCATTERGORIES BOARD GAME ON THE STUDENTS VOCABULARY MASTERY AT SEVENTH GRADE OF Mts PONDOK PESANTREN ULUMUL QUR’AN MEDAN YEAR 2020/2021 - Alfi, Talitha Almira (BRIGHT VISION Journal of Language and Education, 2021)
The research was conducted to find out the effectiveness of using scattergories board game in teaching vocabulary which was observed from the students’ at seventh grade of Mts Pondok Pesantren Ulumul Qur’an Medan. The method used was quantitative research method by using quasi experimental research. The population of this research was seventh grade of Mts Pondok Pesantren Ulumul Qur’an Medan. In taking the sample of the research, the researcher used saturated sampling which took all of the students’ in seventh grade. The classes divided into experimental class and control class. There were 23 students’ experimental class and 22 students’ in control class. In experimental class was taught by using Scattergories board game and in control class was taught by using expository method. In experimental class the increase of the mean score was 21.96 and in control class the increase of the mean score was 14.97. Based on the T-test result by using SPSS V.22 in experimental class and control class, it was found that Sig. score was 0.001. It means that the Sig. core was smaller than 0.005 (0.000 < 0.05). It can be conclude that there were significant differences between experimental class and control class. Therefore there was effectiveness of using Scattergories Board Game in teaching vocabulary at seventh grade of Mts Pondok Pesantren Ulumul Qur’an Medan. Keywords: Vocabulary, Students, Scattergories Board Game